Comparison of Health Care Utilization: United States versus Canada. (25th September 2012) - Pylypchuk, Yuriy; Sarpong, Eric M.
Abstract : Objective: To compare health care utilization between Canadian and U.S. residents. Data Sources: Nationally representative 2007 surveys from the Medical Expenditure Panel Survey for the United States and the Canadian Community Health Survey for Canada. Study Design: We use descriptive and multivariate methods to examine differences in health care utilization rates for visits to medical providers, nurses, chiropractors, specialists, dentists, and overnight hospital stays, usual source of care, Pap smear tests, and mammograms. Principal Findings: The poor and less educated were more likely to utilize health care in Canada than in the United States. The differences were especially pronounced for having a usual source of care and for visits to providers, specialists, and dentists. Health care use for residents with high incomes and higher levels of education were not markedly different between the two countries and often higher for U.S residents. Foreign‐born residents were more likely to use health care in Canada than in the United States. The descriptive results were confirmed in multivariate regressions. Conclusions: Given the magnitude of our results, the health insurance structure in Canada might have played an important role in improving access to care for subpopulations examined in this study.